Faktor Risiko Obesitas pada Guru Sekolah Perempuan serta Relevansi dengan PTM Selama Pandemi Covid-19 - Agus Hendra Al Rahmad (Amerta Nutrition, 2021)
Background: The prevalence of obesity in the world is getting higher, so it becomes a severe health problem. Some factors that contribute to the problem of obesity are increased calorie intake, including the consumption of junk food and sedentary, and low physical activity. School teachers are one of the most crucial labor elements in improving the human development indeks.Objectives: The study aims to determine the risk factors for obesity in female teachers as well as some non-communicable health problems during the Covid-19 pandemic.Methods: This quantitative study uses a cross-sectional design, which was conducted on 270 female school teachers; the sample was taken by purposive sampling. Participants measured weight, height, waist circumference data. Blood pressure data were also recorded by participants, including data on diabetes, cholesterol, arthritis, coronary heart disease. While the BMI value data is calculated by the researcher Data collection using a questionnaire distributed from Google Form. Statistical analysis using test Chi-Square and Logistic Regression. Results: The results showed risk factors for obesity in female school teachers were age, waist circumference, consuming junk food, type of diet and physical activity (p< 0.05), with the main predictor being consumption junk food (OR= 3.2). Also, obesity in women is closely related to several non-communicable diseases such as hypertension and arthritis.Conclusions: The main risk factors that cause the high prevalence of obesity in female school teachers in Banda Aceh City are due to consumption habits junk food during the Covid-19 pandemic, and are strongly related to health problems such as hypertension and arthritis.